Combining field‐amplified sample stacking with moving reaction boundary electrophoresis on a paper chip for the preconcentration and separation of metal ions. Issue 3 (5th January 2017) - Ouyang, Liangfei; Liu, Qian; Liang, Heng
Abstract : A common drawback of paper‐based separation devices is their poor detection limit. In this study, we combined field‐amplified sample stacking with moving reaction boundary electrophoresis on a paper chip with six array channels for the parallel separation and concentration of multiple samples. With a new hyphenated technique, the brown I2 from the Fe 3+ /I − oxidation–reduction reaction emerged near the boundary between the dilute ethylene diamine tetraacetic acid and potassium iodide and highly concentrated KCl solutions. For the separation and concentration of three components, Cr 3+, Cu 2+, and Fe 3+, the Fe 3+ detection limit was improved at least 266‐fold by comparing the hyphenated technique with moving reaction boundary electrophoresis. The detection limit of Fe 3+ was found to be as low as 0.34 ng (20 μM) on the paper chip. We also demonstrated the analysis of a real sample of four metal ions, with detection limits as follows: 0.16 μg Cr 3+, 1.5 μg Ni 2+, 0.64 μg Cu 2+, and 1.5 μg Co 2+ . The synergy of field‐amplified sample stacking and moving reaction boundary electrophoresis in the micron paper‐based array channels dramatically improved the detection limit and throughput of paper‐based electrophoresis.